2018
DOI: 10.12688/gatesopenres.12888.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of market segmentation and social marketing on uptake of preventive programmes: the example of voluntary medical male circumcision. A literature review

Abstract: Background: The business world has long recognized the power of defining discrete audiences within a target population. However, market segmentation’s full potential has not been applied to the public health context. While some broad elements of market segmentation (e.g., age, geography) are considered, a nuanced look at behavioural and psychographic segmentation, which could greatly enhance the possibility of lasting behaviour change, is often missing.   Segmentation, and the associated mindset which acknowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Our study uses the segmentation approach (Sgaier et al 2018) to identify HIV vulnerability profiles for AGYW living in sub-Saharan Africa. While segmentation approaches have long been used in business and marketing fields, their application in global public health efforts remains limited (Gomez et al 2018). Notable exceptions include a study in Malawi that examined HIV risk perception and self-efficacy dimensions to better inform the development of tailored HIV prevention messages to different subgroups of men and women (Rimal et al 2009), work in Zambia and Zimbabwe on understanding the underlying drivers for men's decisions for voluntary medical male circumcision, and work in Niger around developing profiles of women's willingness to adopt family planning (Camber Collective 2015; Dalglish et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study uses the segmentation approach (Sgaier et al 2018) to identify HIV vulnerability profiles for AGYW living in sub-Saharan Africa. While segmentation approaches have long been used in business and marketing fields, their application in global public health efforts remains limited (Gomez et al 2018). Notable exceptions include a study in Malawi that examined HIV risk perception and self-efficacy dimensions to better inform the development of tailored HIV prevention messages to different subgroups of men and women (Rimal et al 2009), work in Zambia and Zimbabwe on understanding the underlying drivers for men's decisions for voluntary medical male circumcision, and work in Niger around developing profiles of women's willingness to adopt family planning (Camber Collective 2015; Dalglish et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Segmentations may be based on demographic, geographic, psychographic or behavioural characteristics of the target population [22]. Despite difficulties in measuring the impact of these approaches, there is evidence to suggest that psycho-behavioural segmentations, which incorporate data on motivations, behaviours and beliefs, result in more homogeneous (and therefore recognisable and useful) segments than a purely demographic analysis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In public health, segmentation has been applied to understand perceptions of HIV risk in Malawi, barriers to VMMC in Zambia and Zimbabwe, and needs and preferences for family planning technology in Niger [26][27][28]. However, it has been noted that these methods are used relatively rarely to target health interventions [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…The personalization of health care content may have bearing on the issue of engagement. Studies have shown that it is possible to segment the population according to the likelihood of responding to health care messages [ 74 , 75 ]. Although our framework provides the best evidence available relating to engagement with web-based content, the holy grail may lie in developing further the field of psychographics for health care.…”
Section: Discussionmentioning
confidence: 99%